Kommunalreformens konsekvenser: Kommunalpolitikernes rolle, borgernes lokaldemokratiske opfattelse og den administrative organisering - Olsen, Asmus Leth (Politik, 2010)
This article reviews the empirical literature on the consequences of the municipal amalgamations under the Danish Municipal Reform of 2007. Specifically, three areas of research are reviewed: the role of local coun- cilors, the perception of local democracy among citizens and administrative organizational changes. First, the research points to lower perceived influence among local councilors of amalgamated councils. However, these trends have not affected the degree of voluntary retirement among councilors or the strong consensual norm of Danish local politics. Second, studies point to substantially reduced internal and external political efficacy among citizens in amalgamated municipalities. Furthermore, the negative effects seem to be dependent on the degree of amalgamation. Third, the amalgamations have had varied impact on organizational changes with increased horizontal division of the administration and the number of citizen service centers on one hand, and at the same time no shift in the use of contracting out or the use of internal contracts. Finally, the article points to consequences of the reform of which we still need to gain a better understanding.